Islamic Arts and Crafts - Milwright, Marcus.
1 online resource (273 pages)
Keywords: This anthology of written sources (dating from the seventh to the twentieth centuries) explores numerous aspects of the crafts of the Middle East from the processing of raw materials to the manufacture of finished artefacts.